The Search for World Order and the Wars in Kosovo and Iraq. Issue 1 (March 2021) - Ellison, James
Abstract : In the search of world order after the Cold War, two conflicts were of particular significance. The first, in Kosovo in 1999, was fought to end the Serbian genocide of Kosovar Albanians. The second, in Iraq in 2003, was a war of choice ostensibly to remove the threat of Saddam Hussein's Iraqi regime and the weapons of mass destruction it supposedly held. Although distinct, these wars were joined as attempts by the United States governments of Bill Clinton and George W. Bush, either side of the 9/11 attacks, to answer the questions of how, and for what purposes, the US should use its power, and what form of international order it should seek. One foreign leader, the British Prime Minister Tony Blair, sought to influence the Americans in answering these questions. As a result, the Anglo-American relationship was once again important in shaping the course of global affairs. Why and how the wars produced cooperation between two US presidents and Blair, and how ideas about international order featured, are the subjects of this article.